Solutions and Three-Dimensional Consistency for Nonautonomous Extended Lattice Boussinesq-Type Equations. Issue 2 (October 2016) - Feng, Wei; Zhao, Song-lin
Abstract : In this paper, we investigate the nonautonomous extended lattice Boussinesq-type equations in terms of generalized Cauchy matrix approach. Several kinds of solutions more than multi-soliton solutions to these equations are derived by solving determining equation set. Three-dimensional consistency of these equations is also studied.